(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The possible influence of transgenic Event 176 com on the development of the mite Tetranychus urticae Koch was evaluated for the first and the second generation. Laboratory studies were carried out on transgenic and isogenic com using this phytophagous mite, measuring the time of development of the different stages, the survival of both sexes and the abundance of eggs laid and hatched. The results do not highlight significant differences between the parameters studied.